The Effect of Multilateralism, Regionalism, and Open Regionalism Towards Exports: ASEAN-5 Study Case - Lubis, Mawar Winona (Journal of Developing Economies, 2016)
Conceptually elimination or reduction of trade barriers through a Regional Trading Arrangement would increase export and import in the region. Trade diversion would take effect and make member countries buy each other goods and services that become cheaper. Open regionalism is another regionalism concept in which the parties involved promise to extend lower tariffs concession not only to member countries but also to other trading partners. This will hinder member countries to reap the benefit of trade diversion. This study examines the effect of Regionalism (after AFTA was fully effective) and Open Regionalism (after Open Regionalism was fully effective for more developed APEC members) on ASEAN-5 countries' export. Using ARIMAX model, the results show that regionalism has a significant yet negative effect on Malaysia and The Philippines and a positive significant effect on Singapore, whereas it is not significant for Indonesia and Thailand's exports. Open regionalism is shown to be not significant for Indonesia, Thailand, and The Philippines exports but it has a negative significant impact for Singapore and Malaysia's exports. Keywords: Trade, Export, Regionalism, Open Regionalism, Multilateralism, ASEAN JEL: F55, F15